Identification of Optimized Spot Welding Parameters for Advanced Automotive Steels - Singh, Amarjeet Kumar; D. Satish Kumar (Engineering Science & Technology, 2025)
Due to the increasing demand to reduce weight-to-strength ratios in the automotive industry, the use of Advanced High Strength Steel (AHSS) materials has grown significantly. In automotive assembly, a number of components are welded to achieve structural stability, making the weldability of the materials a critical aspect in their design and selection. Therefore, in this study, commonly used automotive steel grades-IF 270, TRIP 690, DP 780, and TRIP 980 materials-were selected, and a welding study was conducted. Since a welding experiment is time- and resource-consuming, a simulation method was developed. A model incorporating thermo-mechanical and metallurgical phenomena was developed using SYSWELD software (a welding and heat treatment simulation software by ESI Group) to simulate the resistance spot welding processes. This study provides critical current value mappings for various phenomena during resistance spot welding of automotive-grade steels. It was observed that, with the increase in welding current, weld diameter and failure load increase before expulsion. Predictions of nugget size and Heat-Affected Zone (HAZ) using the developed model match well with experimental results.